Answer:
11
Step-by-step explanation:
4=1
14=2
24=3
34=4
40=5
41=6
42=7
43=8
44=9
45=10
46=11
You will encounter 11 4s.
Answer:
D
Step-by-step explanation:
Answer:
It is +2 or since (+2)*(+2 ) gives. If you think that it would be (-2) also then you are wrong because root of a positive rational number is always positive number.
Step-by-step explanation:
Let the square root of four be ‘k’.
Then we have
(4)^1/2=k
(Squaring both sides)
4=(k)^2
=>(k)^2–4=0
=>(k)^2-(2)^2=0
=>[k+2][k-2]=0 {since (a)^2-(b)^2=(a+b)(a-b)}
if product of two numbers is 0 then either of one must be zero.
If k+2=0 then k=-2
If k-2=0 then k=2
From here we got two answers but -2 should be omitted because when we square an equation we add “root extra”which means that when we square an equation one root is added.
A. C = 17h + 15
b. 83 = 17h + 15
-15 - 15 subtract 15 from both sides
68 = 17h
------------
17 divide both sides by 17
4=h
They cleaned the house for 4 hours
c. C = 20x
to do this last part, you would put both equations into the calculator under y=, then look at the table to determine when the price is the same. According to the calculator, the price is the same at 5 hours
Answer:
Here Ariel is wrong because 3x^3 is higher power than y^2
3x^3 goes first
then the mixed term -4x^2y
then the y^2
then the 2
So, Marcus is right
Standard form means that you write the terms by descending degree. here's main rules how to write polynomial expression in the standard form:
1. write the term with the highest exponent first (terms of third degree in our case 3x^3 );
2. write the terms with lower exponents in descending order (term -4x^2y followed by y^2
);
3. remember that a variable with no exponent has an understood exponent of 1 (here are no such terms);
4. a constant term (a number with no variable) always goes last (term 2).